(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present study reported an eco-friendly process for quick synthesis of silver nano particles (Ag-NPs) using an aqueous leaf extract of Corchorus Capsularis, with an aim to investigate the new and effective and cheap nano-therapeutic approach to P. Aeruginosa, staphylococcus aureus and coagulase negatives (CoNS,CRCP). At various intervals the formation of stable Ag-NPs usually provides range from 5 to 45 nm in diameter to spherical particles. The resultant Ag-NPs were analyzed by ultra-violet spectroscopy (UV-Vis), Fourier infra red transform (FT-IR), X-ray diffraction (XRD), Electron Microscopy (TEM) and Energy, Dispersive Radiation Analytics (EDM) (EDX). XRD analysis indicates that the particles with face centered cubic shape are crystalline in nature. The production of Ag-NPs at 20.52 nm is shown by the TEM study. Multi Drug Resistant (MDR) P. Aeruginosa, Staphylococcus Aureus and CoNS isolates from post-surgical wound infections were examined for antibacterial activity from synthesized Ag-NP. This research demonstrates that Ag-NPs produced using CRCP aqueous leaf extract have considerable antibacterial activity in post-chirurgical wound isolates.